RESULTS OF THE COMPARATIVE STUDY ON THE ONSET AND FREQUENCY OF OCCUPATIONAL ALLERGIC CONTACT DERMATITIS AMONG WORKERS IN THE RUBBER AND CONSTRUCTION INDUSTRIES - Nedeva, Marija; Paravina, Mirjana (Acta medicae Medianae, 2025)
Occupational skin diseases are changes in the skin and its adnexa which occur under the influence of various exogenous and endogenous factors. They can be caused by irritants or allergens (irritant or allergic contact dermatitis). To examine the impact of the work environment and occupational hazards concerning the occurrence of Occupational Allergic Contact Dermatitis (OACD), a study on workers in the rubber and construction industries diagnosed with contact dermatitis (CD) was conducted. The structure of the workers was presented according to sex, place of residence, age, qualifications, years of service, type of allergen and work position. The importance of medical, occupational, and social rehabilitation was emphasized, as well as prevention measures (professional orientation, education and health education of the workers). The following conclusion was reached—in the construction industry, men are more frequently affected and there is a higher risk of OACD, although a longer time of exposure is required. The causing allergens are varied. It is imperative to register those affected by the disease and to undertake the corresponding measures of treatment and prevention.